2021
DOI: 10.1007/s12144-021-01373-8
|View full text |Cite
|
Sign up to set email alerts
|

Personal values as early predictors of emotional and cognitive empathy among medical students

Abstract: The present study contributes to the literature by examining the association between personal values (PVs), assessed with the Schwartz’s Portrait Values Questionnaire, and empathy, assessed with the Davis’ Interpersonal Reactivity Index, in a sample of first-year medical students. We also examined medical students’ PVs profile and gender differences in terms of PVs. All participants (N = 398) were Italian, young (average age = 19.62 years, SD = 1.22), and unmarried; none had children. Zero-order correlations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Academic education and early training experiences have the potential to foster as well as to impair empathy (Brunero et al, 2010). Hence, there is a growing interest in detecting the dispositional variables, such as attachment styles (Ardenghi et al, 2020a), personal values (Ardenghi et al, 2021b), emotion regulation (Ardenghi et al, 2021d;Salvarani et al, 2020), patientcentered orientation (Ardenghi et al, 2020b), self-efficacy and personality traits (Barbaranelli et al, 2021) to nurture healthcare students and professionals' empathic competencies and decrease emotional distress. In this pursuit, research has detected several skills and qualities linked to empathy which also characterized dispositional mindfulness (DM) including receptivity, non-judgmental attitudes, active listening, the ability to free the mind from distractions, and to remain in the "here and now" (Ardenghi et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Academic education and early training experiences have the potential to foster as well as to impair empathy (Brunero et al, 2010). Hence, there is a growing interest in detecting the dispositional variables, such as attachment styles (Ardenghi et al, 2020a), personal values (Ardenghi et al, 2021b), emotion regulation (Ardenghi et al, 2021d;Salvarani et al, 2020), patientcentered orientation (Ardenghi et al, 2020b), self-efficacy and personality traits (Barbaranelli et al, 2021) to nurture healthcare students and professionals' empathic competencies and decrease emotional distress. In this pursuit, research has detected several skills and qualities linked to empathy which also characterized dispositional mindfulness (DM) including receptivity, non-judgmental attitudes, active listening, the ability to free the mind from distractions, and to remain in the "here and now" (Ardenghi et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, feeling grateful for what one has and believing personal achievements to be part of a transcendent reality may motivate wanting to support others and disapproving policies or processes that disfavour some groups. The pattern of relationship between ST and support for AFF and SDO is supported by research findings that have linked ST to empathy towards other people and prosocial behaviour (Ardenghi et al, 2021;Łowicki et al, 2020;Pantaléon et al, 2019;Sugiura et al, 2020).…”
Section: Discussionmentioning
confidence: 63%
“…This result could be attributed to females being inherently more orientated towards care for others than males. Females have been shown to be more empathic and tolerant because socialisation for females emphasises the ethics or morals of care (Ardenghi et al, 2021;Schwartz & Rubel, 2005). Lastly, age and gender were not associated with ST, JWB, AFF, and SDO.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They found that females scored higher than men on the value of universalism in over 80% of these samples. This gender difference has also been reported for young adults (Ardenghi et al, 2021) and for 7 to 11-yearold children (Döring et al, 2015). Outside Schwartz's theoretical framework, review studies conclude that females tend to express more concern, and report stronger environmental attitudes and behaviors than men (Gifford & Nilsson, 2014;Zelenzny, Chua, & Aldrich, 2000).…”
Section: Gender Differencesmentioning
confidence: 74%